BRAIN GATE - Kotian, Shruti (International Journal of Students’ Research in Technology & Management, 2015)
As the power of modern computers grows alongside our understanding of the human brain, we move closer to making some pretty spectacular science fiction into reality. Consider the potential to manipulate computers or machinery with nothing more than a thought! Thousands of people around the world suffer from paralysis and loss of other bodily movement, rendering them dependent on others to perform even the most basic tasks. The mind-to-movement system that allows a quadriplegic man to control a computer using only his thoughts is a scientific milestone. This is the BRAIN GATE system.Â Brain gate system is based on â€˜Cyber kineticsâ€™ platform technology to- sense, transmit, analyze and apply the language of neurons. A computer chip, which is implanted into the brain, monitors brain activity in the patient and converts the intention of the user into computer commands. It would be a huge therapeutic application for people who have seizures, which leads to the idea of a â€˜pacemaker for the brainâ€™.